A controlled study of lifestyle treatment in primary care for children with obesity. Issue 3 (21st November 2012) - Mårild, S.; Gronowitz, E.; Forsell, C.; Dahlgren, J.; Friberg, P.
Summary What is already known about this subject Lifestyle intervention is the most common treatment strategy for children with obesity. Specialized units for the care of children with obesity report significant effects of lifestyle treatment. In children, the physical activity component in lifestyle treatment is often well accepted. What this study adds Two lifestyle treatment programmes in primary care for children with obesity both gave a reduction of body mass index significantly greater than the change observed in a non‐intervention comparison group of children with obesity. Substituting one‐third of nurse‐led treatment sessions with sessions led by physiotherapists in one of the programmes did not improve the outcome. The efficacy of treatment in primary care seems to be comparable to that reported in the literature. Objective To evaluate the efficacy of lifestyle treatment in primary care for children with obesity. Methods In a multicentre study, sixty‐four 9‐ to 13‐year‐old children with obesity were randomized to one of two 12‐month lifestyle treatment programmes. The only difference between the programmes was that a physiotherapist substituted the nurse in one‐third of the sessions in an attempt to stimulate physical activity. For comparison, children with normal weight and overweight, and an age‐, sex‐ and body mass index‐matched non‐intervention group of children with obesity were used. Results Anthropometry and laboratory data differed significantly between children with obesity and normal weight at baseline. The follow‐up at the end of treatment was attended by 55 children with obesity, 28 and 27 in each treatment arm. The mean (standard deviation) body mass standard deviation score changed by −0.36 (0.3) in the arm involving a physiotherapist and by −0.33 (0.2) in the other arm. These outcomes were not significantly different. Both reductions were significantly greater than the change of −0.14 (0.3) observed in the non‐intervention comparison group of children with obesity Conclusion The efficacy of treatment in primary care for children with obesity seems to be comparable to that reported in the literature. ISRCTN44919688.